2021
DOI: 10.1146/annurev-genom-121520-081242
|View full text |Cite
|
Sign up to set email alerts
|

Brain Somatic Mutation in Aging and Alzheimer's Disease

Abstract: Somatic mutations arise postzygotically, producing genetic differences between cells in an organism. Well established as a driver of cancer, somatic mutations also exist in nonneoplastic cells, including in the brain. Technological advances in nucleic acid sequencing have enabled recent breakthroughs that illuminate the roles of somatic mutations in aging and degenerative diseases of the brain. Somatic mutations accumulate during aging in human neurons, a process termed genosenium. A number of recent studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 136 publications
(185 reference statements)
0
33
0
Order By: Relevance
“…Recent studies have found that pTau promotes neuronal cell cycle reentry and the subsequent aneuploidy, hyperploidy, and somatic mosaicism documented in both viral infections and neurodegenerative disorders ( Knight and Robertson, 2004 ; Dove et al., 2006 ; Mosch et al., 2007 ; Lopes et al., 2009 ; Arendt, 2012 ; Miller et al., 2021 ). Indeed, other novel studies have revealed that pTau can destabilize the genome, activating transposable element (TE), a hallmark of cancer and neurodegeneration ( Grundman et al., 2021 ).…”
Section: Cell-cell Fusion and Tau Hyperphosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have found that pTau promotes neuronal cell cycle reentry and the subsequent aneuploidy, hyperploidy, and somatic mosaicism documented in both viral infections and neurodegenerative disorders ( Knight and Robertson, 2004 ; Dove et al., 2006 ; Mosch et al., 2007 ; Lopes et al., 2009 ; Arendt, 2012 ; Miller et al., 2021 ). Indeed, other novel studies have revealed that pTau can destabilize the genome, activating transposable element (TE), a hallmark of cancer and neurodegeneration ( Grundman et al., 2021 ).…”
Section: Cell-cell Fusion and Tau Hyperphosphorylationmentioning
confidence: 99%
“…In return, this pathology may alter glial homeostasis, contributing to neuronal loss by neurotoxic astrocytes and microglia ( Liddelow et al., 2017 ; Zhang et al., 2020 ). In this regard, phenomena previously associated with both neurodegeneration and viral infections, including neuronal cycle reentry, aneuploidy, hyperploid DNA, and somatic mosaicism, may be explained by fusion-mediated multinucleation ( Knight and Robertson, 2004 ; Dove et al., 2006 ; Mosch et al., 2007 ; Lopes et al., 2009 ; Arendt, 2012 ; Miller et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Age-dependent accumulation of somatic mutations has been associated with aging and neurodegenerative cases ( 4 , 5 ). Multiple studies have identified a low allele frequency of mutations of genes causing the familial form of NDDs in human brains ( 6 ). For example, mosaicism from the somatic mutation of presenilin-1 was identified in 14% of cortical cells in a patient with AD.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, somatic (chromosomal and single-gene) mosaicism appears to be a mechanism for human interindividual diversity, development and aging (Campbell et al, 2015;D'Gama and Walsh, 2018;Iourov et al, 2012;Heng, 2019;Vijg, 2014). More precisely, monogenic and chromosomal diseases, neurodevelopmental/neurobehavioral and neuropsychiatric disorders, neurodegeneration, cancer and healthy/unhealthy aging are associated with a wide spectrum of somatic genomic mosaicism types (D'Gama and Walsh, 2018;Iourov et al, 2012;Heng, 2019;Vijg, 2014;Iourov et al, 2019;Yurov et al, 2019;Vorsanova et al, 2020;Ye et al, 2020;Miller et al, 2021;Iourov et al, 2021a;Iourov et al, 2021b). According to the Genome Architecture Theory, somatic mosaicism-mediated heterogeneity is essential for cellular adaptation, and at the same time, as an evolutionary trade-off, somatic mosaicism may be a disease mechanism, as well (Heng, 2019;Ye et al, 2019;Iourov et al, 2020;Iourov et al, 2021b;Heng and Heng, 2021).…”
Section: Editorial On the Research Topic Somatic Genomic Mosaicism An...mentioning
confidence: 99%